Evaluasi dan Optimalisasi Kinerja Unit Accelerator Pada IPAM Ngagel II Kota Surabaya - Fadhilah Labibah Nurjanah; Okik Hendriyanto Cahyonugroho (Jurnal Serambi Engineering, 2024)
IPAM Ngagel is one of the drinking water purification plants (IPAM) owned by PDAM Surya Sembada Surabaya City as a provider of clean water needs for the people of Surabaya City. In order to meet the demand for clean water, the raw water used in the Ngagel Water Treatment Plant has to pass through several treatment units. However, there are several obstacles that result in the treatment unit not operating optimally. Therefore, this research aims to evaluate and compare the performance of one of the treatment units, the accelerator unit. This research method includes field studies, literature studies, data analysis and interviews using data in the form of inlet and outlet water quality of the accelerator unit and the use of coagulant doses for 20 days. The results obtained for the percentage removal in accelerator 1 are turbidity 90.32%, organic compounds 18.76%, ammonia 46.04% and nitrite -2.40%. While the percentage removal in accelerator no. 3 is 84.23% turbidity, 15.75% organic compounds, 25.68% ammonia and -19.48% nitrite. Based on the evaluation results, the removal efficiency in accelerator number 1 is better than that in accelerator number 3. This is because the operations in the accelerator unit, particularly the use of coagulant doses, are not in accordance with what is required, and this affects the difference in the performance of the accelerator unit.